Policy Compliance and Ritual Maintenance Dilemma: Can Chinese Folk Temples’ Air Pollution Control Measures Ensure Visitor Satisfaction? - Wang, Kuo-Yan; Yu, Jing (Frontiers in Environmental Science, 2022)
In recent years, the environmental authorities in Taiwan have begun paying attention to the management of burning incense and joss paper during the Chinese folk belief worship process due to it being a source of air pollution. However, because of the specific religious comfort function, as well as the corresponding economic and social influence of the folk temple itself, devout believers and visitors tend to be more concerned about the temple’s environmental measures under the new policy implementation. Chinese folk temples are a good case study, as they strongly represent the sacrificial habits of many residents on the island. The present study was conducted with this framework in mind. The main objectives include exploring the following: (1) the attitudes of the visitors toward air pollution control in the temple, (2) their willingness to visit after the worshipped temple improves air quality, and (3) factors affecting the worshippers’ visit intention and policy satisfaction. Descriptive statistics and binary logistic regression were utilized. Findings strongly suggested that the visitors’ attitudes toward air pollution control in this area were positive. For air pollution control in the temple, the survey revealed that visitors’ education level and place attachment were the main factors affecting their visit intention and policy satisfaction. The current study lays a solid foundation for decision-making in further controlling air pollution and promoting public participation through community-based environmental policies in similar areas.